+331G/A variant in the progesterone receptor gene, postmenopausal hormone use and risk of breast cancer - Kotsopoulos, Joanne (2009)
A functional promoter polymorphism in the progesterone receptor (PR) gene previously has been associated with an increased risk of postmenopausal breast cancer. Whether the relationship between genetic variation in PR and risk of breast cancer is modified by postmenopausal hormone (PMH) use is unknown. Thus, we conducted a case-control study nested within the prospective Nurses’ Health Study to evaluate if the risk of breast cancer associated with having the +331 A risk allele was modified by PMH use. Genotyping of this SNP was available for 1664 postmenopausal breast cancer cases and 2391 controls. Logistic regression was used to estimate the odds ratios (ORs) and 95% confidence intervals (CIs) for breast cancer. Women who were carriers of one or both variant A alleles had a 31% increased risk of developing breast cancer (95%CI 1.04-1.65). PMH use significantly modified the association between the +331G/A polymorphism and risk (P-interaction <0.05). Among never users of PMH, women who were variant carriers had a significantly increased risk of breast cancer compared to those with the wild-type genotype (OR=2.57; 95%CI 1.64-4.02). The +331G/A polymorphism was not associated with breast cancer risk among past (OR=1.23; 95%CI 0.77-1.97) or current (OR=1.14; 95%CI 0.84-1.56) PMH users. The data from this large prospective study provide evidence for a two-fold increased risk of developing postmenopausal breast cancer among never users of PMH with the +331G/A SNP. This finding adds to the evidence that the progesterone receptor has an important etiologic role in breast cancer and should be evaluated in future studies.